2011
DOI: 10.1149/1.3575637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Electrochemical Behavior of CeCl3 in Molten LiCl-KCl Eutectic Utilizing Metallic Ce as an Anode

Abstract: A study of the electrochemical behavior of CeCl 3 in LiCl-KCl eutectic was performed in the temperature range 653-973K to ascertain if CeCl 3 is a suitable surrogate for UCl 3 in the development of nuclear fuel cycle technologies. Reduction of cerium occurs in a single 3-electron step that is quasi-reversible. The diffusion coefficient of Ce(III) was determined by linear sweep voltammetry and chronopotentiometry. The standard potential of Ce(III)/Ce(0) was measured and used to calculate Gibbs free energy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 33 publications
4
47
1
Order By: Relevance
“…In most of the studies, measurements have been made simply by visual determination of the immersion depth, 4,14,17,[22][23][24][25][26][27][28]32,33,39,42,[49][50][51][52][53]58 which has an error associated with capillary effects and wetting between the electrode and the salt at different temperatures. Several studies used wires encased in alumina or other insulating material tubes with a known apparent surface area.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the studies, measurements have been made simply by visual determination of the immersion depth, 4,14,17,[22][23][24][25][26][27][28]32,33,39,42,[49][50][51][52][53]58 which has an error associated with capillary effects and wetting between the electrode and the salt at different temperatures. Several studies used wires encased in alumina or other insulating material tubes with a known apparent surface area.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, there have been many quantitative studies completed for the electrodeposition of lanthanide elements (Er, Ce, Tb, Gd, etc.). Both, A-S and S-H theoretical models have been used to study the electrodeposition of cerium (Ce 3+ /Ce 0 ), 22 26 reported, in CV studies of LiCl-KCl-ErCl 3 on a tungsten electrode, an observable "crossover" between the positive and negative scan curves. The reason for this behavior has been linked to the difference between the potential required for the formation of stable nuclei on an inert surface…”
mentioning
confidence: 99%
“…The cost of instrumentation is relatively low, thus inexpensive [25], and some of these techniques like stripping voltammetry are highly sensitive [26] and selective which can be used up to ppm and ppb level determinations [27]. Therefore, stripping voltammetry is a promising technique for the determination of palladium in high level nuclear waste since dealing with the least amount of nuclear materials is also important because of the radioactivity issue [28].…”
Section: Introductionmentioning
confidence: 99%